Analysis of The Philosophy and Meaning of The Singkawang Dayak Tatung - Kartika, Ayuni; Anzani, Nazwa; Tiara, Veronika; Liska, Fransiska; Budiharto, Sutoyo (Universitas Tanjungpura, 2025)
Culture is the foundation of social existence and a dynamic guide to life, adapting to the advancement of globalization. In Indonesia, ritual plays a crucial role as a medium for strengthening solidarity and transmitting noble values. One important ritual is the Tatung Dayak Singkawang Tradition in West Kalimantan, a product of the acculturation of the Dayak and Chinese ethnicities. This tradition was recognized as an Intangible Cultural Heritage of Indonesia in 2020 and features supernatural practices such as invulnerability, symbolizing courage and warding off disaster. Previous studies have emphasized phenomenological and functional approaches, but gaps remain in understanding the ontological and epistemological dimensions of this tradition. This study aims to analyze the deeper meaning and spiritual values behind the Tatung Dayak Singkawang Tradition. Using a qualitative approach with George Herbert Mead's symbolic interactionism design, subjects were selected through purposive sampling: Tatung artists of Chinese ethnicity. Data were collected through semi-structured interviews and analyzed using the Miles and Huberman techniques, including data reduction, presentation, and conclusion drawing. The results demonstrate that Tatung is not merely a performance, but a spiritual-social process for achieving communal balance and protection. Possession by ancestral spirits is considered a guardian, shaping the construction of the spiritual self (The Self) and legitimizing invulnerability as a symbol of spiritual purity and a barrier against negative energy. Key rituals such as street washing and ward off disaster reflect the collective hope of the Singkawang community for safety (Generalized Other). Cultural acculturation is reflected in costumes and language that adapt to the identity of the possessing spirit, not the Tatung ethnicity. Compliance with taboos emphasizes the internalization of collective hopes to maintain the sacred role of the Tatung. Overall, this tradition is a system of symbolic interactions that shape and maintain the Collective Self based on the hope of cleansing and safety.